Cost-effective Ethernet Communication for Low Cost Microcontroller Architecture - Horvat, Goran; Šoštarić, Damir; Balkić, Zoran (International Journal of Electrical and Computer Engineering Systems, 2012)
With the advancement of microelectronic technology and the overall rising trend in the use of low cost microcontrollers the need to share information over the existing infrastructure is more and more emphasized. The problem that persists is how to implement Ethernet communication in low cost microcontrollers while retaining low cost of the device. This paper proposes the use of Microchip’s Stand-Alone Ethernet Controller ENC28J60 in order to establish Ethernet communication towards the application located on a Host PC. In order to reduce the induced overhead on the existing Microcontroller firmware size, the paper proposes the use of User Datagram Protocol (UDP) alongside with added authentication in the form of Basic Access Authentication using the Base64 algorithm to establish communication. The communication is tested using the Atmel AVR microcontroller architecture (Atmel AVR XMEGA) and the Stand-Alone Ethernet Controller whereas the sent data is displayed on a National Instruments LabVIEW application running on a Host PC. The measurement is carried out by using network protocol analysis and the comparison is made against the existing communication protocol (TFTP). The proposed communication is compared to one of the existing protocols, Trivial File Transfer Protocol (TFTP). The results are visible in a higher data rate and a lower flash size for implementation, representing an advantage over the existing protocols.